2021
DOI: 10.1021/acs.est.1c04635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metal Ions on Aqueous-Phase Decomposition of α-Hydroxyalkyl-Hydroperoxides Derived from Terpene Alcohols

Abstract: We report the results of a mass spectrometric study of the effects of atmospherically relevant metal ions on the decomposition of αhydroxyalkyl-hydroperoxides (α-HHs) derived from ozonolysis of α-terpineol in aqueous solutions. By direct mass spectrometric detection of chloride adducts of α-HHs, we assessed the temporal profiles of α-HHs and other products in the presence of metal ions. In addition, reactions between α-HHs and FeCl 2 in the presence of excess DMSO showed that the amount of hydroxyl radicals fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…We recently found that the reaction of α-Tp α-HHs with Fe 2+ is outcompeted by H + -catalyzed decomposition of α-HHs at ambient concentrations of Fe 2+ and H + found in atmospheric condensed phases. 38 Further work to test the effects of structures and functionalities on the decomposition of ROOHs in the aqueous phase is underway. Our theoretical calculations imply the existence of different reaction pathways, such as water-catalyzed reactions, that could be correlated with the fates of α-AHs in ambient particles under variable relative humidity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently found that the reaction of α-Tp α-HHs with Fe 2+ is outcompeted by H + -catalyzed decomposition of α-HHs at ambient concentrations of Fe 2+ and H + found in atmospheric condensed phases. 38 Further work to test the effects of structures and functionalities on the decomposition of ROOHs in the aqueous phase is underway. Our theoretical calculations imply the existence of different reaction pathways, such as water-catalyzed reactions, that could be correlated with the fates of α-AHs in ambient particles under variable relative humidity.…”
Section: Resultsmentioning
confidence: 99%
“…15 A previous iodometry analysis of a mixture of 1 mM a-Tp + 0.2 mM NaCl + 0.06 mM O 3 + 0.1 mM HCl revealed that approximately 70% of O 3 was converted into H 2 O 2 and other peroxides in water. 38 Another experimental study on the aqueous-phase decomposition of aacyloxyalkyl-hydroperoxides derived from a-pinene CIs with carboxylic acids found that H 2 O 2 is a key decomposition product. 39 Comparison of the activation energies for the decomposition of a-AHs and related ROOHs in aqueous solutions…”
Section: Theoretical Calculations For the Decay Of A-ahs In The Aqueo...mentioning
confidence: 99%
“…Next, we performed measurements of mass spectra with the use of H 2 18 O and D 2 O. O solution, non-shifted signals at m/z 341;343 appeared initially, but they gradually shifted to m/z 343;345 (Fig. 3).…”
Section: Isotope Experimentsmentioning
confidence: 99%
“…We have recently investigated the condensed-phase fates of a-hydroxyalkyl-hydroperoxides (a-HHs) and a-alkoxyalkyl-hydroperoxides (a-AHs) derived from the reaction of terpenoid-derived CIs with water and alcohols, respectively. [16][17][18][19][20][21][22][23] We have successfully detected C 11-13 a-AHs derived from the reaction of a-terpineol (a monoterpene-alcohol, a-Tp) CIs with monohydric alcohols as their chloride-adducts via on-line electrospray mass spectrometry in aqueous solutions. 23 We have found that the a-AHs decompose faster at lower pH, leading us to propose that the decompositions are catalyzed by H + .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation